2016
DOI: 10.1021/acs.inorgchem.6b01108
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorescent Molecular Butterflies with Controlled Potential-Energy Surfaces and Their Application as Luminescent Viscosity Sensor

Abstract: We report precise manipulation of the potential-energy surfaces (PESs) of a series of butterfly-like pyrazolate-bridged platinum binuclear complexes, by synthetic control of the electronic structure of the cyclometallating ligand and the steric bulkiness of the pyrazolate bridging ligand. Color tuning of dual emission from blue/red, to green/red and red/deep red were achieved for these phosphorescent molecular butterflies, which have two well-controlled energy minima on the PESs. The environmentally dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…The red‐shift can be rationalized by an accurate analysis of the electronic structure of the bimetallic complexes. The HOMO of the bimetallic platinum(II) complex with short a Pt−Pt distance, is in general, the antibonding σ*5dz2-5dz2 molecular orbital [6e,13] . During the excitation process, an electron is removed from an antibonding molecular orbital, resulting in a stabilization of the Pt−Pt bond (Figure S23).…”
Section: Figurementioning
confidence: 99%
“…The red‐shift can be rationalized by an accurate analysis of the electronic structure of the bimetallic complexes. The HOMO of the bimetallic platinum(II) complex with short a Pt−Pt distance, is in general, the antibonding σ*5dz2-5dz2 molecular orbital [6e,13] . During the excitation process, an electron is removed from an antibonding molecular orbital, resulting in a stabilization of the Pt−Pt bond (Figure S23).…”
Section: Figurementioning
confidence: 99%
“…Pt­(II) complexes have shown promise in applications of organic light-emitting diodes and photocatalysts. Previous studies of cyclometalated Pt­(II) dimer complexes with a pseudo-2-fold symmetry demonstrated structurally tunable photophysical properties . As the Pt–Pt distance decreases in the ground state due to stereohindrance exerted by the bridging ligand, the lowest-energy electronic transition transforms from a ligand-centered (LC) and/or metal-to-ligand-charge-transfer (MLCT) transition localized on one-half of the molecule to a metal-metal-to-ligand-charge-transfer (MMLCT) transition delocalized over the entire molecule. As the Pt­(II)–Pt­(II) distance decreases, the interactions of the 5d z 2 molecular orbitals (MOs) between the two Pt­(II) atoms become stronger, causing a larger energy splitting between the dσ bonding MO and dσ* antibonding MO (HOMO) and thus increasing the HOMO energy. Consequently, the lowest-energy electronic transition is transformed to the MMLCT in nature, dominated by the HOMO­(dσ*)–LUMO­(π*) transitions and red-shifted in the ground-state absorption spectra. , The MMLCT transition depletes an electron from the antibonding dσ* orbital and adds the electron density to the antibonding π* ligand-centered orbital, thereby effectively increasing the Pt–Pt bond order by ∼0.5 and shortening the Pt–Pt distance by ∼0.3–0.5 Å in the MMLCT excited state. , Consequently, the Pt–Pt stretching vibrational frequency will be higher in the excited state than in the ground state.…”
mentioning
confidence: 99%
“…Considering the similarity of this temperature-dependent dual emission of [Pb 3 Cl 11 ] 5– to those of platinum molecular butterfly complexes and low-dimensional metal halide hybrids with two emitting excited states, we propose the presence of two triplet energy minima on the excited-state potential energy surface in this bulk assembly of [Pb 3 Cl 11 ] 5– clusters, as shown in Figure C. As the formation of two different emitting excited states likely involves structural distortion, a kinetic energy barrier between two emitting excited states with distinct distorted structures is expected. The structural distortion of [Pb 3 Cl 11 ] 5– clusters on the excited state, on the other hand, could be affected by their molecular environment; that is, a less compact and soft matrix would lead to easier structural distortion. Therefore, the excited-state dynamics for (bmpy) 9 [ZnCl 4 ] 2 [Pb 3 Cl 11 ] can be described as follows: At low temperature with rigid molecular environment for [Pb 3 Cl 11 ] 5– clusters and low thermal energy, the photogenerated excitons localized in the emitting state 1 (ES1) have difficulty overcoming the energy barrier to reach the emitting state 2 (ES2), resulting in mainly blue emission.…”
mentioning
confidence: 99%